2017
DOI: 10.33584/jnzg.2017.79.564
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in the nutritive composition of four forage species at high and low N fertiliser

Abstract: Chicory and plantain have been suggested as alternative grazed forages to perennial ryegrass for New Zealand dairy systems. While diurnal changes in plant chemical composition have been described for ryegrass there is currently little information for herbs. This experiment aimed to compare the effect of nitrogen inputs (low and high) and harvesting time (am versus pm) on the chemical composition of four forages (ryegrass, plantain, chicory and white clover). The effect of harvest time was greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…For herb species, chicory and plantain, Minnee et al (2017) measured greater soluble carbohydrates (14%) compared with perennial ryegrass (7%). Conversely, Box et al (2017a) reported greater WSC for perennial ryegrass (23%) compared with chicory (19% WSC) or plantain (20% WSC). The discrepancy in ranking between herbs and grasses may be a product of the environmental conditions or analytical procedures as the two studies report carbohydrates in different terms.…”
Section: Increased Soluble Carbohydratementioning
confidence: 89%
See 3 more Smart Citations
“…For herb species, chicory and plantain, Minnee et al (2017) measured greater soluble carbohydrates (14%) compared with perennial ryegrass (7%). Conversely, Box et al (2017a) reported greater WSC for perennial ryegrass (23%) compared with chicory (19% WSC) or plantain (20% WSC). The discrepancy in ranking between herbs and grasses may be a product of the environmental conditions or analytical procedures as the two studies report carbohydrates in different terms.…”
Section: Increased Soluble Carbohydratementioning
confidence: 89%
“…In perennial ryegrass, the majority of these carbohydrates are extractable in water and are primarily fructan and sucrose (White 1973). Interestingly, although Box et al (2017a) measured more WSC in ryegrass compared with herbs, a greater proportion of the total DM for plantain was not accounted for. In plantain, for instance, L-arabinose accounts for 20-25% of the sugars (Brautigam and Franz 1985;Kardošová 1992) but it is unlikely to be detected in routine laboratory methods for WSC using anthrone reagents (Jiang et al 2019).…”
Section: Increased Soluble Carbohydratementioning
confidence: 96%
See 2 more Smart Citations
“…Two experiments investigating the effects of regrowth interval (Study 1), fertiliser and additives (Study 2) on plantain silage, were conducted under irrigation at the Lincoln University Research Dairy Farm, Canterbury, New Zealand (43º64'S, 172º46'E). The plantain pastures (cultivar 'Tonic') were established following cultivation in March 2014 and were rotationally grazed with dairy cows (Box et al 2017). On 14th November 2016 the experimental area for both studies (0.60 ha) was mown to 6 cm.…”
Section: Experimental Site and Treatmentsmentioning
confidence: 99%